Dampak Penerapan Prinsip Pendidikan Inklusi di PAUD Inklusi Saymara Kartasura: Penelitian - Naura Huwaida; Hery Setiyatna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyse the impact of applying inclusive education principles at Saymara Inclusive Early Childhood Education on child development. The study uses a qualitative approach with in-depth interviews, aiming to understand the experiences and meanings felt by educators in applying inclusive education principles. The implementation of inclusive education principles is carried out by providing equal opportunities for regular children and children with special needs, as well as implementing an Individual Learning Programme (PPI) tailored to the needs and potential of each child. Learning activities involve social interaction and independence training to encourage the development of emphathy, helpfulness, and social skills in children. The obstacles that arise include the challenges of managing diverse classes and the lack of support from some parents for the inclusion programme. Nevertheless, the implementation of inclusive education has a significant positive impact, including improving children’s social and communication skills and self-confidence, as well as shaping the social character of regular children. The results of the study confirm that inclusive education not only supports the development of children with special needs but also creates an adaptive, equitable learning environment that values the diversity of student.